LA REGULACIÓN DE LOS DERECHOS EN LOS NUEVOS ESTATUTOS DE AUTONOMÍA - Enriqueta Expósito (Revista d'Estudis Autonòmics i Federals, 2007)
One of the most significant new features that is included in the new statutesof autonomy are the so-called territorial declarations or charters of citizens'rights. The aim of this study is to analyse this from two different but complementaryperspectives. From a more general point of view, it is a synthesis ofthe arguments that have been used by Spanish nationalist constitutionalistdoctrine in favour of or against the new contents of the statutes, in an attemptto highlight how neither of them are the key to a decision on whetheror not the declarations of rights in the statutes are inappropriate or unconstitutional.From a more specific point of view, there is a more detailed examinationof the contents of these charters – the regulatory framework in whichthe new texts of the statutes is included, which rights are proclaimed and whatare the guarantees surrounding the proclamation in the recent statutes. Inits conclusions, the study clearly shows that first, the charters are in full agreementwith the nature and function of the statutes in the Spanish autonomousregional state. Second, that these charters are regulations which as faras the citizen is concerned, complement constitutional rights and bring themup to date them with new content.